How do Indigenous People in Kjipuktuk Conceptualize Poverty? A Qualitative Study Exploring the Relationship of Impoverishment to Health - Rae, Madeline; Robinson, Margaret (Atlantis, 2026)
This pilot study examines Indigenous conceptualizations of poverty in Kjipuktuk, Mi’kma’ki (Halifax, Nova Scotia) to lay groundwork for a holistic model of Indigenous poverty that can link with holistic models of Indigenous health already in use. Using community-based methods and Mi’kmaw cultural practices, the researchers conducted sharing circles and interviews with 12 Indigenous participants who had experienced or were still living in poverty. Results strongly supported the distinctiveness of Indigenous experiences of poverty and identified starting points for a holistic poverty model.